Perancangan Sistem Informasi Administrasi Jasa Keamanan Berbasis Web Studi Kasus: PT Pasopati Guardian Security Services - Obaja Marum Lumbanraja (TeIKa, 2021)
Companies need integrated information technology capable of supporting the company's performance. Information Technology continues to grow rapidly, fills every field of the company with the system. One area or field that did not miss from Information Technology is field of Administration. PT Pasopati Guardian Security Services need an administration information system that help them to improve the company's performance and reduce the loss for the company. There were 4 goals of this research: 1) Improving the employee performance in doing his job. 2) Reducing unnecessary losses due to irregular available data. 3) Reducing the use of paper in the recording of data security force members, clients, financial expenses and income. 4) Saves time in searching existing data when needed. The methodology used in this research is SDLC (System Development Life Cycle) method which consists of five phases there are: (1) Requirement Analysis, (2) System Design, (3) Coding, (4) Testing and (5) Implementation. From the research that has been done, the authors conclude that: (1) The system that was built is able to improve the performance of employees in doing his job, (2) The system that was built is able to store and display data of financial expenses and income in accordance with the actual data so the data of old and new can be analyzed properly, (3) The system that was built is able to integrate data between members of the security force and client so we can know the number of members in the client's location, and (4) The system that was built is able to help users to make the invoice before the due date of payment by the client and reduce losses that may occur.